Strange I've seen that face before : Objekt, Gestalt, Phantom. - Bradley, Will; Burgess, Anthony; Evans, Cerith Wyn; Kafka, Franz; Kusama, Yayoi; O'Sullivan, Tom; Tatham, Joanne; Titz, Susanne; Webster, Toby (Köln : DuMont, 2006)
Andre, Carl ; Arad, Ron ; Boyce, Martin ; Buren, Daniel ; Consemüller, Erich ; Creed, Martin ; Crichton, Rory ; Danke, Raphael ; Dresser, Christopher ; Evans, Cerith Wyn ; Export, Valie ; Fischer, Urs ; Fontana, Lucio ; Funk, Lissy ; Genzken, Isa ; Hollein, Hans ; Hughes, Richard ; Johannesson, Sture ; Johns, Jasper ; Judd, Donald ; Klucis, Gustav ; Kusama Yayoi ; Leckey, Mark ; LeWitt, Sol ; Mendini, Alessandro ; Moholy-Nagy, Laszlo ; Reyle, Anselm ; Sarcevic, Bojan ; Shrigley, David ; Sonnier, Keith ; Sottsass, Ettore ; Starling, Simon ; Strunz, Katja ; Thomkins, André ; UFO ; Uklanski, Piotr ; Warhol, Andy ; Warren, Rebecca ; Wright, Richard
Strange I've seen that face before, Museum Abteiberg, Mönchengladbach, 2006-05-07. 2006-09-17
boek